Optimizing regulatory T cells for therapeutic application in human organ transplantation. Issue 5 (October 2018) - Vaikunthanathan, Trishan; Safinia, Niloufar; Lombardi, Giovanna
Abstract : Purpose of review: Initial clinical trials of adoptive regulatory T-cell (Treg) therapy in solid organ transplantation have proven to be both feasible and well tolerated. With Phase 2 trials underway, efforts have been focused on the optimization of the Treg product. Recent findings: With science and our knowledge on the biology of these cells constantly advancing, we have been able to refine our search for a Treg population that would be ideally suited for therapeutic application. This idealized population must be readily isolated, allow for in-vitro expansion, demonstrate potent and specific suppressor function, maintain lineage stability and demonstrate a relevant homing profile. With the advent of innovative cell analysis/isolation techniques and genetic modifications, we are able to choose and design Tregs to fulfil these criteria. Summary: By utilizing advances in science and technology, we can optimize Treg therapy in human organ transplantation maximizing their prospects in the arena of transplantation tolerance.